THREE-DIMENSIONAL FINITE ELEMENT ANALYSIS OF DELAMINATION BUCKLING OF COMPOSITE LAMINATES WITH CONTACT EFFECT AT THE INTERFACES OF DELAMINATION - XIONG Ying; XUE JiangHong; CHEN ShuHua; ZHANG JianWen; XIA Fei (Jixie qiangdu)
This paper presents a finite-element approach to simulate the buckling process of the composite laminated plate containing a buried delamination. The delaminated composite laminates are analyzed using solid elements. In order to prevent the mutual penetration between the two parts above and below the delamination and to ensure coordinated deformation, a normal behavior of hard contact is applied at the interfaces of the delamination to take into consideration of the nonlinear contact effect between the debonded regions. Parametric analyses are conducted to investigate the effects of delamination depth, delamination length and aspect ratio on the buckling loads. Furthermore, buckling of a perfect laminate with the same geometrical parameters is simulated to obtain the critical buckling load. A comparison between the finite element prediction and the classic theoretical solution for the perfect laminate is carried out. It is found that they are in good agreement. The established model can simulate the buckling process of the composite laminated plate accurately.